Market, economy and geology of strategic metals - Toledo Garay, Fernando Enrique (2001)
The market, economy and geology of the strategic metals involve interdisciplinary fields of knowledge, to visualize the importance and the use of metals in order to economically attractive, and to look for the alternatives of their commercialization and search in the terrestrial crust. The has been analyzed because they are denominated strategic and its has been that the developed countries the they require with urgency due to the shortage with which it is in the terrestrial crust and in their territories, as well as the urgency with which the warlike and peaceful industry needs it to continue the technological and economic advance of these countries.